Tupoksi Manajemen Pendidik Dan Tenaga Kependidikan Dalam Upaya Meningkatkan Mutu Pendidikan Menuju Era Society 5.0 - Elsa Sakinah; Wati Rohmawati; Wilda Rahayu (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Writing This article tries to explain the main tasks and functions of educator management which are part of national education standards. This research is applying a qualitative descriptive method with the type of research used, namely the study of literature from various sources such as books and journals. The research findings show that the management of the duties and functions of educators and education staff is carried out in accordance with statutory regulations with the aim of increasing national education standards, advancing science, technology and the arts, as well as providing physical education for the local population. Six elements make up the implementation of the responsibilities and functions of educators and education management: planning, recruitment, placement, coaching, employment and evaluation. Management functions and tasks are useful for schools in overcoming the shortage of teachers and education personnel through recruitment. Individual learning, training and further education are also used in construction and development; both are run by working groups of instructors, schools, and the education office.